Self-organisation in photoactive fullerene porphyrin based donor-acceptor ensembles - Guldi, Dirk Michael; Luo, Chuping; Swartz, Angela; Scheloske, Michael; Hirsch, Andreas (Chemical Communications, 2001)
Complexation of ZnP-C-ZnP triads with diazabicyclooctane (DABCO) leads to rigid assemblies that display considerably prolonged charge-separated states.